Maternal Health-Related Quality of Life and Its Predicting Factors in the Postpartum Period in Iran - Nazanin Rezaei; Arman Azadi; Razieh Zargousi; Zinab Sadoughi; Zahra Tavalaee; Maryam Rezayati (Scientifica)
Background/Purpose. Postpartum period is accompanied by many physical, emotional, and social changes in women’s health. The aim of this study was to examine the mothers’ quality of life in postpartum period. In addition, it also sought to recognize the variables that predict their quality of life. Methods. This cross-sectional, descriptive study was undertaken among 380 women in 10 urban health centers in Ilam province in west of Iran. They were selected using proportional random sampling method. The SF-36 questionnaire was used to identify women’s health-related quality of life (HRQoL). Data were analyzed using SPSS version 15. Results. Women who were employed, aged less than 30 years, had college degree, have no history of disease in pregnancy, and had given birth more than 3 months ago had higher quality of life scores. Independent predictors for lower physical HRQoL were being with history of disease in pregnancy; being with high school diploma or lower education; and giving birth less than 3 months ago. Also, independent predictor for lower mental HRQoL was being housewife. Conclusion. According to study findings, greater attention must be paid to providing postpartum healthcare for housewife and less educated women as well as those with history of disease in pregnancy.